Entre las organizaciones de base y los gobiernos: Las experiencias de la sociedad civil con los PRSP. Un estudio de la respuesta de la sociedad civil local a los PRSP - Susanne Possing (Danish Institute for International Studies (DIIS), 2003)
– The report focuses on civil society experience with locally identified priorities for poverty eradication, an area little examined and less discussed in the international debate on PRSP to date. In the three N/S PRSP Programme countries, Honduras, Nicaragua and Zambia, civil society organisations have been involved in efforts to identify national as well as local priorities for poverty eradication. Taking the point of departure in involvement of CS with PRSP planning and monitoring at both levels, the paper presents a range of challenges and dilemmas for civil society in its efforts to combat poverty. Special attention is given to civil society initiatives and response to PRSP in provinces, districts and communities. In the three countries civil society organisations carry out projects aimed at poverty eradication at local levels, some initiated in relation to PRSPs, some initiated regardless of and before initiation of the national PRSP process. Three areas stand out as critical for local CSOs: (i) Women's contributions must be regarded as an asset in poverty eradication, (ii) Focus on rural development – support to peasants and other small producers, (iii) Promotion of local production and local trade. Major efforts of civil society organisations (and INGOs) have been directed upwards towards lobbying at national and international levels. While well justified, this focus advances the risk of neglecting local civil society initiatives in communities and districts. There is a need to support a process that encourages citizens and local civil society organisations to engage in a long-term commitment in municipalities and villages.
Keywords: 330; Armutspolitik; Gemeinwesenarbeit; Honduras; Nicaragua; Sambia